Vitamin C as Prevention in Burn Sepsis - Tanuwijaya, Lucretya Yeniwati (Lingkar Studi Bedah Plastik Foundation, 2020)
Background: Burns is a severe public health problem. Its poor treatment can lead to the worst complication called sepsis. Since sepsis decreases the immune system, the critical therapy management of burn sepsis ensures adequate end-organ perfusion. According to the Surviving Sepsis Campaign Bundle, immediate identification and management in the initial hours generate a better outcome. The inflammation of burn injury is known to increase ROS production, which causes cellular damage, sepsis, and MODS. This condition initiates the importance of ROS scavenger. Methods: This literature reviewed from relevant works of literature which searched from major journal databases of WHO, Pubmed, Elsevier, JAMA, Springer, NEJM, which published from 2013 until 2018 Results: Vitamin C is a cheap but effective antioxidant, which acts as a ROS scavenger and reduces the fluid requirement in burn resuscitation for the prevention of burn sepsis Conclusion: Vitamin C could be recommended as adjuvant therapy in the prevention of burn sepsis